Маркетинговий рейтинг як фактор конкурентоспроможності підприємства - Маковоз, Оксана Сергіївна (Медобори-2006, 2016)
Досліджено процес формування маркетингових рейтингів підприємство щодо оцінки успішності їх діяльності. Проаналізовано основні дефініції сутності конкурентоспроможність підприємства, запропоновано основні складові маркетингового рейтингу підприємств щодо оцінки рівня їхньої конкурентоспроможності. Охарактеризовано сучасний стан складання рейтингів підприємств щодо оцінки наявних та виявлення можливих ресурсів.

The process of forming of the marketing rating is investigational enterprise in relation to the estimation of success of their activity. Basic definitions of essence are analysed competitiveness of enterprise, the basic constituents of the marketing rating of enterprises are offered in relation to the estimation of level of their competitiveness. The modern state of stowage of rating of enterprises is described in relation to the estimation of present and exposure of possible resources.
Marketing rating as factor of competitiveness of the enterprise
Keywords: рейтинг; конкурентоспроможність; підприємство; потенціал; оцінка; маркетинговий рейтинг; rating; competitiveness; enterprise; potential; estimation; marketing rating